2008
DOI: 10.1039/b715251e
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive rolling and bending of thin crystals of chiral diarylethenes

Abstract: Dithienylhexafluorocyclopentene with (R)- or (S)-N-phenylethylamide substituents formed rod-like and 0.2-1.0 microm-thick platelike crystals by sublimation; upon UV irradiation, the crystals bent concavely to the incident light and finally rolled crystals were obtained; the bent crystals were reconverted to flat crystals by visible light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
98
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 12 publications
3
98
1
Order By: Relevance
“…This is because the geometric changes required to change from one state to the other are minimal. Indeed photochemistry is preserved even in crystalline states (66)(67)(68). Initial attempts to study the photoswitching of diarylethenes selfassembled on a surface of gold nanoparticles showed that when the switching unit is isolated from the surface by a linker based on a pentamethylene alkyl chain, the photochromism of the compound is retained (69), with both ring closure and ring opening on gold nanoparticles proceeding in a manner similar to that observed in solution.…”
Section: Photoswitchable Molecularly Modified Nanoparticlesmentioning
confidence: 99%
“…This is because the geometric changes required to change from one state to the other are minimal. Indeed photochemistry is preserved even in crystalline states (66)(67)(68). Initial attempts to study the photoswitching of diarylethenes selfassembled on a surface of gold nanoparticles showed that when the switching unit is isolated from the surface by a linker based on a pentamethylene alkyl chain, the photochromism of the compound is retained (69), with both ring closure and ring opening on gold nanoparticles proceeding in a manner similar to that observed in solution.…”
Section: Photoswitchable Molecularly Modified Nanoparticlesmentioning
confidence: 99%
“…The photomechanical crystals have attracted much attention because they can work without any direct contact or electrical wires [9]. Various types of photomechanical behaviors such as contraction [8,10], expansion [11], OPEN ACCESS bending [8,[11][12][13][14][15][16][17], separation [18], twisting [19], and rolling [12] have been reported so far. Although photochromic compounds such as diarylethenes [8,19], furylfulgide [20], azobenzene [21,22], anthracene carboxylates [23][24][25][26][27][28], salicylideneaniline [29], 4-chlorocinnamic acid [30], 1,2-bis(4-pyridyl)ethylene salt [31], benzylidenedimethylimidazolinone [32], and others [33] exhibit photochemical reactions in the crystalline phase, their photomechanical motions in the crystal are almost bending.…”
Section: Introductionmentioning
confidence: 99%
“…Some diarylethene crystals thus far have been reported to cause the photoinduced reversible bending. [4][5][6][7][8] In the present case, the contraction is considered to occur in the diagonal direction. When irradiated with UV light, the photoisomerization of the diarylethene molecules from the open-ring isomer 1 a to the closed-ring isomer 1 b occurs in the crystalline phase.…”
mentioning
confidence: 99%
“…Single microcrystals of diarylethenes have been found to exhibit rapid and reversible macroscopic changes in shape and size upon irradiation with UV and visible light. [4][5][6][7][8] Recently, 9-anthracenecarboxylic acid (9AC) crystals have been shown to twist upon UV light irradiation. [11] 9AC can undergo a reversible [4+4] photocyclodimerization in the crystalline phase.…”
mentioning
confidence: 99%
See 1 more Smart Citation